Physical functioning and health-outcomes following hospitalisation with COVID-19: a longitudinal cohort study - O'Brien, Kate (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Introduction: A novel coronavirus (severe acute respiratory syndrome coronavirus 2; SARS-CoV-2) emerged in Wuhan, China in late 2019, causing an outbreak of viral pneumonia. Initial studies published focused on the management of acute COVID-19 and the containment of the virus. The wide range of clinical presentations of acute COVID-19 is well-documented from asymptomatic infection to death. Published studies suggest short-term physical recovery from COVID-19 is complex, with many individuals experiencing persistent symptoms. There is a paucity of data investigating the longer-term trajectory of physical recovery from COVID-19. There have been no studies to-date investigating physical recovery from hospitalisation with COVID-19 amongst an Irish cohort. Methods: This study was conducted in St. James?s Hospital, Dublin. Participants were recruited from the hospital?s Post-Acute COVID-19 Multidisciplinary Clinic from May to November 2020. For Project 1 a prospective longitudinal design was utilised to investigate the impact COVID-19 has on physical functioning at 10-weeks (T1), 6-months (T2) and 1-year (T3) post-hospital discharge. Objective measures of recovery included 6-Minute Walk Test Distance (6MWTD), frailty (Clinical Frailty Scale), quantification of falls following hospital-discharge, return to work status and exercise levels. Subjective markers included symptoms (COVID-19-Specific Patient Concerns Assessment), fatigue (Chalder Fatigue Score) and health-related quality of life (HrQOL) (Short-Form-36 Health Survey Questionnaire). Univariate analysis was performed using t-test, Wilcoxon rank-sum, and Chi-squared test, paired analysis using one-way analysis of variance and Kruskal-Wallis testing and correlation analysis with Spearman correlation tests. At T2 a subset of participants was recruited to participate in Project 2. Project 2 sought to gain a deeper understanding of the lived experience of recovering from hospitalisation with COVID-19 through individual interviews. A total of 18 participants were interviewed. Interviews were recorded and transcribed verbatim. Reflexive thematic analysis was used to interpret and analysis the interview data. Results Project 1: Sixty-one subjects participated. Assessments were conducted at a median of 55 days(T1), 242 days(T2), and 430 days(T3) following hospital-discharge. 6MWD improved significantly overtime (F?=?10.3, p?<?0.001) from 365(209) m at T1 to 447(85)m at T3, however remained below population norms (572m for males and 538m for females) and with no associated improvement in perceived exertion (as assessed by the Modified Borg Scale). Approximately half (n?=?27(51%)) had returned to pre-diagnosis exercise levels at T3. At least one concern/symptom was reported by 74%, 59% and 64% participants at T1, T2 and T3 respectively. Fatigue was the most frequently reported symptom at T1(40%) and T2(49%), while issues with memory/concentration was the most frequently reported at T3(49%). SF-36-II scores did not change significantly in any domain over the study period, and scores remained lower than population norms in the domains of physical functioning, energy/vitality, role limitations due to physical problems and general health. Return-to-work rates are low, with 55% of participants returning to work in some capacity, and 31% of participants don?t feel back to full-health at 1-year following infection. Results Project 2: Participants gave varying accounts of recovery with several over-arching themes emerging including a) a complex recovery experience characterised by persistent symptoms, often which are unpredictable and confusing, b) positive recovery experience with little effect on physical function, c) the effects of the global pandemic and government mandated restrictions on recovery, d) follow-up care and e) return-to-work. Results from Project 2 highlighted the importance of the patient narrative in understanding the complex and individual nature of recovery from COVID-19. Conclusion: Hospitalised COVID-19 survivors report persistent symptoms, particularly fatigue and breathlessness, low health-related quality of life scores, sub-optimal exercise levels and continued work absenteeism 1-year following infection, despite some objective recovery of physical functioning. Findings suggest those who returned to exercise within 1-year may have less fatigue and breathlessness. Future research on the impact of exercise, and other rehabilitative strategies is warranted to explore rehabilitation goals to optimise patient outcomes during recovery from COVID-19.
APPROVED